Discrete mathematical structures - Kolman, Bernard (Pearson, 2009)
This is the International Edition. The content is in English, same as US version but different cover. Please DO NOT buy if you can not accept this difference. Ship from Shanghai China, please allow about 3 weeks on the way to US or Europe. Message me if you have any questions